Monitoring and Evaluation in the United States Government : An Overview - Mark, Katharine; Pfeiffer, John R. (World Bank, Washington, DC, 2017)
This report is divided into five parts. Following this introduction, Section two provides an overview of the institutions and most important features in the landscape of monitoring and evaluation (M&E) at the federal level in the United States. Section three detailed the actual systems for performance M&E that is now in place in the Executive Branch and coordinated (or led) by the office of management and budget, including a look at their evolution and expected future trends. The focus is on the executive system, because it directly supports management and budgeting decisions, and because it provides a key basis for evaluation and research conducted by other agencies (such as the U.S. Government Accountability Office, or GAO and Congressional Budget Office, or CBO). Section four discusses the strengths and particular challenges faced by these systems, and section five concludes the report with lessons that may be useful to other countries.